A review: effect of copper percentage solder alloy after laser soldering - Asyraf, Abdullah; Siti Rabiatull Aisha, Idris (Emerald Group Publishing Limited, 2023)
Purpose This study aims to review the effect of copper percentage in Sn-based solder alloys (Sn-xCu, x = 0–5 Wt.%) on intermetallic compound (IMC) formation and growth after laser soldering.